Isolation and molecular characterization of the hemagglutinin gene of H9N2 avian influenza viruses from poultry in Java, Indonesia - Nugroho, Christian Marco Hadi; Silaen, Otto Sahat Martua; Kurnia, Ryan Septa; Soejoedono, Retno Damajanti; Poetri, Okti Nadia; Soebandrio, Amin (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The avian influenza virus (AIV) subtype H9N2 circulating in Indonesia has raised increasing concern about its impact on poultry and its public health risks. In this study, the H9N2 virus from chicken poultry farms in Java was isolated and characterized molecularly. Materials and Methods: Thirty-three pooled samples of chicken brain, cloacal swab, trachea, and oviduct were taken from multiple chickens infected with AIV in five regions of Java, Indonesia. The samples were isolated from specific pathogenic-free embryonated eggs that were 9 days old. Reverse transcription polymerase chain reaction and sequencing were used to identify H9N2 viruses. Results: This study was successful in detecting and characterizing 13 H9N2 isolates. The sequencing analysis of hemagglutinin genes revealed a 96.9%–98.8% similarity to the H9N2 AIV isolated from Vietnam in 2014 (A/muscovy duck/Vietnam/LBM719/2014). According to the phylogenetic analysis, all recent H9N2 viruses were members of the lineage Y280 and clade h9.4.2.5. Nine of the H9N2 isolates studied showed PSKSSR↓GLF motifs at the cleavage site, while four had PSKSSR↓GLF. Notably, all contemporary viruses have leucine (L) at position 216 in the receptor-binding region, indicating that the virus can interact with a human-like receptor. Conclusion: This study described the features of recent H9N2 viruses spreading in Java’s poultry industry. Additionally, H9N2 infection prevention and management must be implemented to avoid the occurrence of virus mutations in the Indonesian poultry industry. J. Adv. Vet. Anim. Res., 8(2): 423-434, June 2021 http://doi.org/10.5455/javar.2021.h530